PERBEDAAN KEKERASAN PERMUKAAN BAHAN RESTORASI RESIN KOMPOSIT NANOFILLER YANG DIRENDAM DALAM MINUMAN RINGAN BERKARBONASI DAN MINUMAN BERALKOHOL - Nurul Ikhsan; Nila Kasuma; Didin Kustantiningtyastuti (Faculty of Dentistry Universitas Andalas, 2016)
Resin composite is dental material filling that is commonly used in dentistry which has good physical properties, mechanical and aesthetics. The properties that have an important role in the resistance of the composite resin surface hardness which directly involved when contact with food, drink and salivary. The purpose of this research is to evaluate the effect of carbonated soft drink and alcoholic beverages on the surface hardness of nanofiller composite resin.The method used in this research is post test only control group design. Samples were made using the mold made of stainless steel, with diameter of 6mm and tick of 2mm, composite was manipulated according to the manufacture’s instructions, and then immersed in aquades, carbonated soft drink and alcoholic beverages for 18 hours in a temperature of 37ºC. Samples were tested using Vickers Hardness Test. Data analysis using Kruskal-Walis test.The result show that the nanofiller composite resin which immersed in alcoholic beverages has higher surface (81,04±10,44 VHN), whreas the composite which immersed in aquades and carbonated soft drink has the surface hardness (70,20±16,6 dan71,10±15,96 VHN). The result of data analysis showed that the data are not distributed normally and showed a significant value of p>0,05. From this research can be concluded that there is no significant differences in surface hardness of nanofiller composite resin which immersed in carbonated soft drink and alcoholic beverages. Keywords: Resin Komposit, nanofiller, surface hardness, mechanical properties.